Drivers of food safety adoption among food processing firms: A nationally representative survey in Ghana - Asante, Seth; Ragasa, Catherine; Andam, Kwaw S. (International Food Policy Research Institute, 2020)
Globally, food system transformation is characterized by the increasing importance of food safety and quality standards for consumers. This trend is challenging for the food processing sector in Ghana, which is dominated by micro and small firms. This study investigates the factors influencing the adoption of food safety practices and the effect of such adoption on the profitability of nationally representative food processing firms in Ghana using instrumental variable approach and matching techniques. The study uses nationally representative data for 511 food processing firms. The data show few food processing firms (20 percent) have adopted food safety practices. Wide diversity of firms was observed, and firm size, firm age, registrations, trainings, processing activities, types of buyers, and number of distinct products explain the differing firm adoption of food safety practices. We also find that adopters of food safety practices earn more per month than do nonadopting firms, implying the presence of economic incentive to adopt food safety practices. Support in terms of food safety awareness and training to food processing firms can help improve adoption of food safety practices.